PENGARUH VARIASI LAMA WAKTU KONTAK DAN JUMLAH TANAMAN KAYU APU (Pistia stratiotes) TERHADAP PENURUNAN KADAR CADMIUM (Cd) LIMBAH CAIR BATIK HOME INDUSTRY “X” DI MAGELANG - Amalia Jamil; Yusniar Hanani Darundiati; Niki Astorina Yunita Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Home Industry Batik “X” in Magelang dispose of batik wastewater directly without wastewater treatment to the environmental. The batik wastewater containing heavy metals Cadmium (Cd), which can have a negative impact, both for environmental and health. The checking result of Cadmium (Cd) of batik wastewater is 1,317 mg/l this number is exceed the standart of Perda Jateng Number 5 2012 th. The purpose of this research to determine the effect of the contact time variations (6 day, 7 day and 8 day) and the number of water lettuce (6 clump and 8 clump) to reduced of cadmium level in wastewater of batik home industry